2007
DOI: 10.1007/s00428-007-0367-x
|View full text |Cite
|
Sign up to set email alerts
|

Search for residual prostate cancer on pT0 radical prostatectomy after positive biopsy

Abstract: Reported incidence of no residual prostate cancer (i.e. pathological stage pT0) on radical prostatectomy ranges from 0.07 to 4.2%. The incidence is higher after neoadjuvant endocrine treatment. The aim of this study was to search for residual cancer on radical prostatectomy (RP) specimens when an initial sampling failed to find the cancer in patients with positive biopsy. Our database of 1,328 consecutive patients whose biopsies and RP specimen were both examined at the Polytechnic University-United Hospitals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 27 publications
1
42
0
3
Order By: Relevance
“…[49][50][51] 56 found an incidence of 0.67% after 10-core positive biopsy to be higher than that previously reported.…”
Section: Radical Prostatectomy Specimens With No Carcinoma On Initialmentioning
confidence: 92%
See 1 more Smart Citation
“…[49][50][51] 56 found an incidence of 0.67% after 10-core positive biopsy to be higher than that previously reported.…”
Section: Radical Prostatectomy Specimens With No Carcinoma On Initialmentioning
confidence: 92%
“…[49][50][51] As an initial step, the needle biopsy should be reviewed to confirm a diagnosis of malignancy. The radical prostatectomy sections should also be reviewed in order to confirm the absence of cancer.…”
Section: Radical Prostatectomy Specimens With No Carcinoma On Initialmentioning
confidence: 99%
“…[9][10][11] Mazzucchelli et al, 9 in a study of 1328 RPs, found 8 cases without residual cancer on RP, for an incidence of 0.6%. Five of these cases were from hormonally treated patients and only 3 from untreated patients.…”
Section: Commentmentioning
confidence: 99%
“…Furthermore, because the possibility of capsular incision in some cases of VC exists (referring to the urologist's transecting either benign or malignant prostatic tissue, consequently leaving prostate or tumor behind), 18 the pathologist should discuss this possibility with the urologist or comment on the pathology report. 9 Finally, a specimen mix-up is another possibility for not finding residual cancer on RP. If significant amount of carcinoma, especially high grade (Gleason score .7), with perineural invasion on the needle biopsy is found and there is no tumor on the RP specimen, switching of the biopsy specimen should be investigated, ideally using molecular tests.…”
Section: Commentmentioning
confidence: 99%
“…Few studies have been published that document the use of DNA profiling to identify prostate biopsy identity errors. 1,[5][6][7][8] In most of these studies, DNA profiling was only used for patients in whom cancer could not be identified within the prostatectomy surgical specimen (pT0 patients) despite testing positive by needle biopsy. Moreover, the number of patients for whom DNA identity profiling was performed in these studies was small, ranging from two to six patients.…”
Section: Discussionmentioning
confidence: 99%